Zuccagnia punctata: A Review of its Traditional Uses, Phytochemistry, Pharmacology and Toxicology - Isla, Maria Ines (2016)
Zuccagnia punctata Cav. (Fabaceae, Caesalpiniaceae) is a plant with a long history of use in Argentine traditional medicines; it belongs to a monotypic genus, and is an endemic species of Argentina. This review provides a comprehensive overview of the traditional uses, phytochemistry, pharmacological activity and toxicology of Z. punctata. A wide range of traditional uses are cited in the literature such as antibacterial, antifungal, anti-inflammatory, and antitumor, among others. Pharmacological studies to date have demonstrated significant activities that support the traditional uses of this plant. No human clinical trials had been completed up to the time of this review and no toxic effect had been detected in animals. Compounds from different chemical groups have been isolated such as phenolic compounds and essential oils. Plant extracts and phytochemicals isolated exhibit a broad range of activities, anti-inflammatory, antibacterial, antifungal, antigenotoxic, antioxidant, antiulcer, and nematicidal. The main bioactive phytochemicals in the aerial parts (leaf, stem and flower) were identified as 2´, 4´-dihydroxy-3´-methoxychalcone and 2´, 4´-dihydroxychalcone and were proposed as chemical markers. Consequently, standardized dry extracts of aerial parts of Z. puntacta could be used in herbal medicinal products. Also, they could be included in phytotherapeutic preparations such as capsules, creams, and gels, and for microencapsulation.